The Effect of Organizational Culture and Compensation on Employee Satisfaction at PT Pertamina Unit Business SPBG Palembang - Gandi Gandi; Neny Rostiati; Roswaty Roswaty (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to analyze the influence of organizational culture and compensation partially on employee job satisfaction, as well as the influence of organizational culture and compensation simultaneously on job satisfaction at PT Pertamina Business Unit SPBG Palembang. The data collection technique used is a questionnaire using a Likert scale. The analysis technique used is multiple regression analysis and thematic analysis. The results of this study indicate that the variables of organizational culture (X1) and compensation (X2) partially have a significant effect on employee job satisfaction. The variable partially has a significant effect on job satisfaction. Simultaneously, the variables of organizational culture (X1) and compensation (X2) have a significant effect on employee job satisfaction. Furthermore, it can be concluded that the two independent variables, namely organizational culture and compensation, have a positive relationship to employee job satisfaction. The results of the study using the correlation test (R) obtained a value of 0.782. This shows that the relationship between organizational culture and compensation together with employee job satisfaction is very strong (78.2%). The results of the final study using the coefficient of determination (R2) obtained a value of 0.588. This shows that organizational culture and compensation variables can explain employee job satisfaction, which is 58.8%, while the rest (41.2%) can be explained by other variables not included in this study. This research is expected to be an additional literacy material regarding employee job satisfaction